Variation of morphological and chemical properties of three varieties of jute stick - Rahman, M Mostafizur; Siddiqua, S; Akter, F; Jahan, M Sarwar; Quaiyyum, MA (Bangladesh Journal of Scientific and Industrial Research, 2016)
Pulp property of a lignocellulosic material depends upon its morphological characteristics and chemical constituents it. Shabuj Pat (CVL-1) variety from Corchorus capsularis and BJRI Tossa Pat 4 (O-72) and BJRI Tossa Pat 5 (O-795) varieties from Corchorus olitorius of jute are mostly grown in Bangladesh. This study deals on morphological and chemical properties of these three varieties of jute stick to assess their suitability for pulp production. The results were significantly differed among the varieties and within the variety. The ?-cellulose content was almost the same in the variety of CVL-1 and O-795. In the same variety, the middle portion contained the largest amount of alpha-cellulose and the top portion contained the lowest. Klason lignin content varied from 24.2 to 26.8%. Fibre length was significantly same for all the three jute sticks but the width and slenderness ratios were different. Pulp yield in soda anthraquinone process was nearly the same in all these varieties around 44% at kappa number 15. Bangladesh J. Sci. Ind. Res. 51(4), 307-312, 2016